2020
DOI: 10.1162/jocn_a_01485
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Symmetrical Gestalts Is Task-Independent, but Can Be Enhanced by Active Regularity Discrimination

Abstract: The brain can organize elements into perceptually meaningful gestalts. Visual symmetry is a useful tool to study gestalt formation, and we know that there are symmetry-sensitive regions in the extrastriate cortex. However, it is unclear whether symmetrical gestalt formation happens automatically, whatever the participant's current task is. Does the visual brain always organize and interpret the retinal image when possible, or only when necessary? To test this, we recorded an ERP called the sustained posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 44 publications
9
57
0
Order By: Relevance
“…We re-ran the regression analysis again and confirmed that flower and landscape SPNs were not statistical outliers. For consistency with Makin et al (2016) , we calculated all SPNs from PO7/8 in the 300–400 ms window (where amplitude is typically maximal), and we only use published SPNs from experiments where participants were explicitly discriminating regularity ( Makin et al., 2015 ; Makin, Rampone, Morris, & Bertamini, 2019 ; Makin et al., 2013 , 2012 , 2016 ; Palumbo et al., 2015 ). Therefore, we used only SPNs from the Symmetry task in the current study, not the Color or Color control tasks.…”
Section: Methodsmentioning
confidence: 99%
“…We re-ran the regression analysis again and confirmed that flower and landscape SPNs were not statistical outliers. For consistency with Makin et al (2016) , we calculated all SPNs from PO7/8 in the 300–400 ms window (where amplitude is typically maximal), and we only use published SPNs from experiments where participants were explicitly discriminating regularity ( Makin et al., 2015 ; Makin, Rampone, Morris, & Bertamini, 2019 ; Makin et al., 2013 , 2012 , 2016 ; Palumbo et al., 2015 ). Therefore, we used only SPNs from the Symmetry task in the current study, not the Color or Color control tasks.…”
Section: Methodsmentioning
confidence: 99%
“…This confirmed that the PCC response was a unique component, with its own distinct time course. Finally (and importantly), Analysis 6 replicated all results from the Regularity task of Makin et al 24 by reanalyzing data from a similar experiment by Palumbo et al 32 .…”
Section: Resultsmentioning
confidence: 52%
“…This investigation involved six analyses, which built on each other to reveal new properties of the brain response to symmetry. In Analysis 1, we re-examined the sensor-level ERP data from Makin et al 24 . In addition to the classic bilateral SPN, we identified a new vertex positivity in the 80 and 100% PSYMM conditions of the Regularity task.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations